Hormone action. - Conn, P. Michael (Methods in enzymology, 1983)
FROM THE PREFACE: A survey of the current biological literature will convince even the most skeptical individual of the substantive and pervasive advances that have occurred in neuroendocrinology. It was the observation that this rapid growth resulted in large part from methodological improvements which first suggested the need for this volume. Some of the advances can be easily recognized. High pressure liquid chromatography, once a tool of the solvent chemist, is now a routine analytical and preparative method in biological laboratories. It has enhanced the speed and resolution with which neuroendocrine substances can be separated. Likewise, peptide synthesis, modification, and analysis are no longer the ken of those whose work is dedicated solely to this task, rather, as one of the authors put it, "almost anyone can synthesize a peptide." Analytical advances have extended the sensitivity and specificity of assay techniques. Culture techniques have been devised which allow us to purify and maintain isolated cells and tissue. In turn, these enhancements have revealed the presence and biological roles of new neuroendocrine substances; in other cases, novel and surprising sites of action have been identified for substances already described.